Das Problem des Fremdpsychischen: Wittgensteins Beitrag und die wissenschaftliche Forschung, insbesondere der Psychoanalyse - Giampieri Deutsch, Patrizia (Bollettino Filosofico, 2019)
Current debates about «Otherness» within Continental Philosophy may be enhanced taking into account the traditional question of solipsism rephrased as «problem of other minds» from Analytic Philosophy and Philosophy of Mind. Philosophy of Mind is no longer an armchair philosophy and is thus looking for viable answers arising from results from empirical research. Accordingly, this contribution considers a number of insights and tentative solutions provided by investigations in current sciences of the mind and sciences of the brain. The starting point of this article is Ludwig Wittgenstein’s multifaceted approach to the other-minds-problem. Considering Wittgenstein’s positions on solipsism, this contribution shows how he overcomes the narrow frame of Analytic Philosophy thus anticipating positions of Philosophy of Mind. Finally, current psychoanalysis in dialogue with its neighbouring disciplines, including Philosophy of Mind, provides some eligible answers to the «other minds problem» intertwining conceptual, clinical and empirical investigations. Keywords: Wittgenstein, Solipsism, Other-Minds-Problem, Philosophy of Mind, Psychoanalysis